Iberian wild leporidae as hosts of zoonotic enteroparasites in Mediterranean ecosystems of Southern Spain. (19th December 2022) - Rego, Laura; Castro‐Scholten, Sabrina; Cano, Carmen; Jiménez‐Martín, Débora; Köster, Pamela C.; Caballero‐Gómez, Javier; Bailo, Begoña; Dashti, Alejandro; Hernández‐Castro, Carolina; Cano‐Terriza, David; Vioque, Fátima; Maloney, Jenny G.; et al.
Abstract: Wild lagomorphs including rabbits and hares can act as natural carriers or reservoirs of bacterial and parasitic zoonotic diseases. However, little is known on the epidemiology and potential public health significance of intestinal eukaryotes in wild leporids. We examined faecal samples from European wild rabbits ( Oryctolagus cuniculus, n  = 438) and Iberian hares ( Lepus granatensis, n  = 111) collected in the Autonomous Region of Andalusia in southern Spain during 2012–2021. We searched for the presence of DNA from the main intestinal protist and microsporidial pathogens of veterinary and public health concerns using molecular methods (PCR followed by Sanger and next‐generation sequencing). Giardia duodenalis was the most prevalent species found (27.8%, 153/550; 95% CI: 24.1–31.8), followed by Cryptosporidium spp. (1.3%, 7/550; 95% CI: 0.5–2.6), Blastocystis sp. (1.1%, 6/550; 95% CI: 0.4–2.4) and Encephalitozoon intestinalis (0.2%, 1/550; 95% CI: 0.0–10.1). All samples tested negative for Enterocytozoon bieneusi . Sequence analyses revealed the presence of sub‐assemblage BIV ( n  = 1) within G. duodenalis, and Cryptosporidium cuniculus ( n  = 6) and Cryptosporidium andersoni ( n  = 1) within Cryptosporidium . The presence of ruminant‐adapted C. andersoni is indicative of a potential cross‐species transmission event, although a spurious infection (mechanical carriage) cannot be ruled out. Samples assigned to C. cuniculus belonged to the gp60 subtype families Va ( n  = 3) and Vb ( n  = 2). The six Blastocystis ‐positive samples were identified as ST2 ( n  = 3) and ST1 + ST2 ( n  = 3). Our molecular results suggest that wild rabbits and hares were primarily infected by leporid‐adapted species of eukaryotic pathogens. However, the occasional findings of zoonotic G. duodenalis sub‐assemblage BIV, Blastocystis sp. ST1 and ST2, and Encephalitozoon intestinalis could be of public health relevance.